Development of an Online Supply Chain Management System for the Pharmaceutical and Cosmetic Industry - Awan Setiawan (INFOKUM, 2023)
An online and responsive (multiplatform) information system that is able to support the work of all employees of cosmetics and medicine distributors who have hundreds of regular customers (shops) in Bandung. Debtors in this company feel that there is a need to update the information system, where the current system still has many shortcomings, and is still semi-manual, thus hampering the performance of employees. This company has sections, each of which has its own separate system. and not integrated, so the flow of business processes often experiences obstacles, for example to issue an invoice, the operator has to use 3 different applications, all three of which still use outdated technology. Salesmen who work in the field need information technology support to support their performance, currently they still use paper lists that are vulnerable to rain. Debtors who still carry out manual matching and recording, and many more. In this report, a new system is described that will be proposed through design using UML (Unified Modeling Language), which generally consists of Use Case Diagrams, Class Diagrams, Activity Diagrams, and Sequence Diagrams . The system built will implement a Cloud ERP (Enterprise Resource Planning) system, which is a concept for planning and managing a company's resources. ERP is an integrated system that aims to summarize existing business processes so that they become an efficient and effective collaboration. This Drug and Cosmetic Distribution Information System was developed using the Laravel framework which is based on the PHP web programming language, development media and MySql for the storage database. Model system development carried out using the waterfall model. The MJM online information system version 2.0 will be able to integrate all parts of the company, and support and facilitate the work of all working parties.